2014
DOI: 10.3758/s13415-014-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

The nature of hemispheric specialization for prosody perception

Abstract: Recent evidence suggests a relative righthemispheric specialization for emotional prosody perception, whereas linguistic prosody perception is under bilateral control. It is still unknown, however, how the hemispheric specialization for prosody perception might arise. Two main hypotheses have been put forward. Cue-dependent hypotheses, on the one hand, propose that hemispheric specialization is driven by specialization for the non-prosody-specific processing of acoustic cues. The functional lateralization hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Estas evidencias permitieron documentar el compromiso de ambos tipos de comprensión prosódica en pacientes con lesiones del HD pero no fueron suficientes para fundamentar la existencia de independencia funcional entre prosodia emocional y lingüística. Los patrones de disociación hallados en el presente trabajo pueden considerarse evidencia a favor de la independencia funcional entre la capacidad de comprender prosodia lingüística y emocional, tal y como habían sugerido varios investigadores (Belyk & Brown, 2014;Caballero, 2016;Joanette et al, 2008;Monrad, 1947;Ross & Monnot, 2008;Witteman et al, 2014;Witteman et al, 2011;Wright et al, 2016). Sin embargo, al no hallarse en nuestro grupo de pacientes con lesiones del HD el patrón de disociación doble en la comprensión prosódica, queda pendiente la realización de trabajos futuros en los que se indague estos patrones en un número mayor de pacientes y/o en otras poblaciones patológicas para apoyar la hipótesis de la independencia funcional con evidencias de doble disociación.…”
Section: Discussionunclassified
“…Estas evidencias permitieron documentar el compromiso de ambos tipos de comprensión prosódica en pacientes con lesiones del HD pero no fueron suficientes para fundamentar la existencia de independencia funcional entre prosodia emocional y lingüística. Los patrones de disociación hallados en el presente trabajo pueden considerarse evidencia a favor de la independencia funcional entre la capacidad de comprender prosodia lingüística y emocional, tal y como habían sugerido varios investigadores (Belyk & Brown, 2014;Caballero, 2016;Joanette et al, 2008;Monrad, 1947;Ross & Monnot, 2008;Witteman et al, 2014;Witteman et al, 2011;Wright et al, 2016). Sin embargo, al no hallarse en nuestro grupo de pacientes con lesiones del HD el patrón de disociación doble en la comprensión prosódica, queda pendiente la realización de trabajos futuros en los que se indague estos patrones en un número mayor de pacientes y/o en otras poblaciones patológicas para apoyar la hipótesis de la independencia funcional con evidencias de doble disociación.…”
Section: Discussionunclassified
“…Rather, they propose that prosodic processing is a multi-step process with differential involvement of both hemispheres. Recent investigations into the lateralization of prosody support this model (Iredale, Rushby, McDonald, Dimoska-Di Marco & Swift, 2013;Paulmann et al, 2013;Witteman et al, 2014).…”
Section: Localizationmentioning
confidence: 93%
“…The late positive response has been observed in experiments where the participant consciously attended to congruency of emotional or prosodic stimuli (Aguado et al, 2013;Chen et al, 2011;Kamiyama et al, 2013). Witteman et al (2014) observed an effect of the late positive potential (LPP) in an emotional task, but not the linguistic one. This effect was larger at posterior sites in the left hemisphere, but proximal sites in the right hemisphere.…”
Section: Late Positive Response Congruency Effect Across Conditionsmentioning
confidence: 99%
“…Patients with LRH may also present difficulties in other competences, such as temporal-spatial orientation, attention, perception (anosognosia, hemineglect, and prosopagnosia) (5) , memory (visual amnesia and working memory) (6) , and emotional processing (comprehension and expression of prosodic stimuli with emotional intonation, emotional processing of faces) (7) . The damage to one or more of the identified components generates distinct profiles of alterations in the expression and verbal comprehension, impairing the quality of life of the individual and their family (8) .…”
Section: Introductionmentioning
confidence: 99%